Analisis Suhu Pada Analyzer Inkubator Bayi Berbasis Formula Mean - Kartika, Wisnu; Supriyadi, Kuat; Sulaimi, Kholid Al; Iswanto, Iswanto (Medika Teknika : Jurnal Teknik Elektromedik Indonesia, 2019)
Baby incubator is an equipment to keep the temperature stability of premature babies. Temperature is an important parameter. Therefore, its stability should be monitored based on the standard required by BPFK (Health Facilities Safety Center) hence the need for calibration. The writer aims to make a calibration tool for baby incubator temperature parameter with four measurement spots. The main sensor from the temperature parameter of incubator analyzer is LM35 as temperature sensor of T1, T2, T3, and T4. The range of temperature that can be detected is between 20.00oC – 50.00oC. The temperature inside the baby incubator has to be between 35.5oC – 37oC. The test was conducted in the baby incubator starting from 32oC – 37oC. The data was collected from the test point value on each temperature spot, the temperature comparison between TA modules used fluke temperature meter as comparison tool and the calibration of baby incubator. The output power for LM35 temperature sensor was done as much as ± 5 times. The biggest error value was found on T4 temperature sensor at ± 1.09762824% and at the temperature of 37oC, while the smallest error value was found on T1 temperature sensor at ± 0.005633803% at the temperature of 35oC. The measurement of baby incubator temperature calibration shows the margin of baby incubator temperature meter ± 1oC at the temperature setting of 32oC, 33oC, and 34oC.